PERAN SISTEM PEMBAYARAN DIGITAL DALAM MENINGKATKAN PRODUKTIVITAS USAHA MIKRO, KECIL, DAN MENENGAH (UMKM) DI KECAMATAN MEDAN PERJUANGAN - Purba, Febri Andriawan; Nasution, Hafizah Mahira; Siregar, Nur Hasanah; Lubis, Sri Nikmah Tullah; Wulandari, Sari (Politeknik Bisnis Indonesia, 2024)
As technology advances, digital payment solutions have emerged as a practical way to streamline transactions and boost MSMEs' operational effectiveness. Data from MSME actors in the area is gathered for this study using a quantitative methodology and survey method. According to the study's findings, MSME productivity is positively impacted by the use of digital payment systems like e-wallets and QRIS. Companies report faster transactions, lower operating expenses, and easier access to larger markets. In addition, digital payment methods contribute to more transparent and accurate financial records. The study's conclusions include the necessity of educating and training MSME participants on the usage of digital payment systems, as well as government and financial institution assistance to promote the technology's uptake. It is envisaged that by taking these actions, Medan Perjuangan District MSMEs will be able to utilize the digital payment system to its full potential and boost their company's sustainability and competitiveness.